An overview of the application of GRACE satellite data in drought research - TANG Yingying; XIAO Liying; GUO Yongcheng; CHENG Yuxiang; LIU Xiangzhou (Renmin Zhujiang)
Drought is a natural disaster that is prevalent on a global scale and has far-reaching impacts on many aspects, including the environment, ecology, economy and society, etc. GRACE (Gravity Recovery and Climate Experiment) gravity satellites can dynamically monitor changes in terrestrial water storage by measuring data on changes in the Earth's gravity field. The spatial and temporal distribution of water storage obtained by GRACE can be used to monitor droughts in order to study the occurrence, development and evolution of drought events. In this paper, the bibliometric method is used to analyze and summarize the current status of the application of GRACE satellite data in groundwater storage changes, meteorological and hydrological drought evolution pattern and response, drought early warning, etc., and the existence of data validation and data interpolation and reconstruction problems. It also looks forward to the research directions of water storage change in changing environment, constructing drought index more suitable for drought monitoring, improving the accuracy of GRACE data, enhancing the temporal and spatial resolution of GRACE data, drought early warning and decision-making support, as well as the response of the regional water cycle and ecosystems, which can provide some reference value for the subsequent related application research.